2017
DOI: 10.1016/j.jmr.2016.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Balanced Steady-State Free Precession (bSSFP) from an effective field perspective: Application to the detection of chemical exchange (bSSFPX)

Abstract: Chemical exchange saturation transfer (CEST) is a novel contrast mechanism and it is gaining increasing popularity as many promising applications have been proposed and investigated. Fast and quantitative CEST imaging techniques are further needed in order to increase the applicability of CEST for clinical use as well as to derive quantitative physiological and biological information. Steady-state methods for fast CEST imaging have been reported recently. Here, we observe that an extreme case of these methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 61 publications
(78 reference statements)
0
25
0
Order By: Relevance
“…Standard CEST imaging at ultra‐high fields has not only demonstrated an easier separation of the peaks but also an increase in the effect strength for amide, amine, and NOE pools . BSSFPX, on the other hand, is expected to show a complex behavior with increasing field strength due to the periodicity of the bSSFP frequency response with 1/TR, which results in CEST‐related asymmetries at pool offsets larger than 1/TR folding back into the profile and consequently an overlap of CEST pools at different chemical shifts …”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Standard CEST imaging at ultra‐high fields has not only demonstrated an easier separation of the peaks but also an increase in the effect strength for amide, amine, and NOE pools . BSSFPX, on the other hand, is expected to show a complex behavior with increasing field strength due to the periodicity of the bSSFP frequency response with 1/TR, which results in CEST‐related asymmetries at pool offsets larger than 1/TR folding back into the profile and consequently an overlap of CEST pools at different chemical shifts …”
Section: Introductionmentioning
confidence: 99%
“…5,6 On the other hand, bSSFP imaging was only recently reported to be intrinsically sensitive to chemical exchange processes leading to asymmetric profiles in isotropic probes of exchanging molecular species. 7 The authors demonstrated based on in vitro experiments that phase-cycled bSSFP, in this context termed bSSFPX, is able to detect chemical exchange processes in solute molecules with small chemical shift differences of the dominant pool close to 1 ppm, such as choline, glucose and glycogen water solutions. The provided contrast in the measured probes related to chemical exchange was observed to be comparable with standard chemical exchange saturation transfer (CEST) measurements.…”
mentioning
confidence: 99%
See 3 more Smart Citations